IMPLEMENTASI KITAB BELAJAR PEGON JAWASEBAGAI INSTRUMEN DALAM MEGEMBANGKAN KETERAMPILAN MENULIS BAHASA ARAB SANTRI BARU PONDOK PESANTREN AN – NUR PUNGGING MOJOKERTO - Fitriyah, Khoirunnisa'il (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2020)
Abstract Key words : Kitab Pegon, ketrampilan Menulis. Islamic boarding schools have many kinds of learning methods used in a formal or non-formal education. Besides that Islamic boarding schools also have a curriculum that is largely to implement learning using the kitab kuning (text books with Arabic language for studying Islam commonly used in Islamic boarding school), bald (without tashkeel/harakah on arabic letters), so it takes a long time to really understand it. Many scholarships must be passed from the aspect of writing, reading and even translating. Therefore, many Islamic scholars who give scientific contributions to come up with easy methods, so the pupils can use it well. One of the contributions is such pego book. This book is small. It provides instructions and guidance on writing Arabic letters with the Javanese language (it’s called pego). The methods are easily understood by new learners. This study aims to know how to implement the pego book in learning Arabic writing at Pondok Pesantren An-Pungging Mojokerto. To achieve it, the researcher used descriptive qualitative research methods. The method is to describe the collected data clearly and specifically. Whereas the data collection techniques used observation, interviews and documentation; the source of the data came from principal, administrators, some teachers who implements ibtida’i method and some students in AN – NUR Islamic Boarding School Pungging Mojokerto. The results of this study show us: 1. The goal is that students can write, read, understand, and translate the bald kitab kuning.